Antibiotics! Does it make a Difference? - Anum Wahid, Irum Sabir Ali, Sana Sahar, Hassan Abbas, Mah Muneer Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: Breast surgeries are classified as clean surgeries but a higher infection rate of 3-15% is noted due to which prophylactic antibiotic is given before surgery. The aim of study is to determine the role of prophylactic antibiotics in malignant breast surgical cases to help in making local guidelines to prevent inadvertent of antibiotics. Matrials and Methods: A Quasi Experimental study was conducted in breast unit of Khyber Teaching Hospital, with sample size of 42 in each group. The study was conducted in 6 months, from January 2023 to June 2023 after taking ethical approval from ethical review committee MTI, KTH. Results: Mean age was comparable between groups (45.18±10.64 vs 49.39±12.02 years; p>0.05). SSI occurred in 13/42 (32.5%) patients without prophylaxis vs 11/42 (25.0%) with prophylaxis (absolute difference 7.5%; p>0.05). Complication severity was similarly low in both arms (Clavien–Dindo 1.23±0.42 vs 1.18±0.45; p>0.05). Although surgical mix differed (BCS 32.5% vs 11.4%; MRM 67.5% vs 88.6% in Groups A vs B, respectively), this did not translate into significant differences in SSI rate or severity. Conclusions: Routine single-dose pre-operative amoxicillin–clavulanic acid did not significantly reduce SSI or alter complication severity following clean breast cancer surgery. These findings support a selective, risk-based approach to antibiotic prophylaxis alongside rigorous peri-operative asepsis, rather than universal prophylaxis. Keywords: breast cancer surgery; surgical site infection; antibiotic prophylaxis; amoxicillin–clavulanic acid; quasi-randomized trial; Clavien–Dindo.